Optimized Batch Fermentation of Cheese Whey-Supplemented Feedlot Waste Filtrate to Produce a Nitrogen-Rich Feed Supplement for Ruminants - Erdman, M. D. (1986)
An optimized batch fermentation process for the conversion of cattle feedlot waste filtrate, supplemented with cheese whey, into a nitrogenous feed supplement for ruminants is described. Feedlot waste filtrate supplemented with cheese whey (5 g of whey per 100 ml) was fermented by the indigenous microbial flora in the feedlot waste filtrate. Ammonium hydroxide was added to the fermentation not only to maintain a constant pH but also to produce ammonium salts of organic acids, which have been shown to be valuable as nitrogenous feed supplements for ruminants. The utilization of substrate carbohydrate at pH 7.0 and 43°C was >94% within 8 h, and the crude protein (total N × 6.25) content of the product was 70 to 78% (dry weight basis). About 66 to 69% of the crude protein was in the form of ammonia nitrogen. Lactate and acetate were the predominant acids during the first 6 to 8 h of fermentation, but after 24 h, appreciable levels of propionate and butyrate were also present. The rate of fermentation and the crude protein content of the product were optimal at pH 7.0 and decreased at a lower pH. For example, fermentation did not go to completion even after 24 h at pH 4.5. Fermentation proceeded optimally at 43°C, less so at 37°C, and considerably more slowly at 23 and 50°C. Concentrations of up to 15 g of cheese whey per 100 ml of feedlot waste filtrate were fermented efficiently. Fermentation of feedlot waste filtrate obtained from animals fed low silage-high grain, high silage-low grain, or dairy rations resulted in similar products in terms of total nitrogen and organic acid composition.